MEKANISME PEWARISAN BITCOIN SEBAGAI ASET KEPEMILIKAN TIDAK BERWUJUD BERDASARKAN HUKUM PERDATA DI INDONESIA: Mekanisme Pewarisan Bitcoin Sebagai Aset Kepemilikan Tidak Berwujud Berdasarkan Hukum Perdata di Indonesia - Iqbal, Iqbal; Nazar, Jazman (UIR Law Review, 2025)
The development of digital technology has brought about new assets such as Bitcoin. However, Indonesian law, particularly the Civil Code, has not yet clearly regulated the inheritance of these digital assets. As a result, legal uncertainty has arisen, particularly regarding how to identify, access, and divide Bitcoin after the owner's death. Technical challenges also arise because access to Bitcoin can only be done with a private key, while there are no legal rules requiring its disclosure. This study aims to examine the status of Bitcoin as an inheritance asset and formulate its inheritance mechanism according to Indonesian civil law. The main questions addressed are: (1) how to establish Bitcoin as an inheritance asset, and (2) how to distribute it after the owner's death. The method used is normative legal research with a descriptive approach. Data sources include the Civil Code, PERMENDAG No. 99/2018, journals, books, and interviews. Analysis is conducted by comparing existing regulations with other intangible assets, such as intellectual property rights, while considering the latest regulatory developments in the crypto field. The research findings indicate that Bitcoin is classified as an intangible movable asset under Articles 503 and 504 of the Civil Code, thereby making it inheritable. The inheritance mechanism requires specific steps, such as asset documentation, digital wills, heir verification, transfers via multi-signature technology, as well as documentation and audits. The main challenges.